RANCANGAN CONTROL DAN MONITORING AFL (AIRFIELD LIGHTING SYSTEM) BERBASIS IOT SEBAGAI SARANA PEMBELAJARAN TARUNA DI POLITEKNIK PENERBANGAN SURABAYA - Dwi Setyo Nugroho (Approach : Jurnal Teknologi Penerbangan, 2021)
Airfield Lighting System (AFL) is a visual landing aid that serves to assist and serve aircraft during takeoff, landing and taxiing in order to move efficiently and safely. The Airfield Lighting System (AFL) includes the following equipment: Runway edge light, Threshold light, Runway end light, Taxiway light, Flood light, Approach light, PAPI (Precision Approach Path Indicator) and VASIS (Visual Approach Slope Indicator System), Rotating Beacon, Turning area light, Apron Light, Sequence Flashing Light (SQFL), Traffic Light, Obstruction Light, WindCone. It is undeniable that the need for a Visual Landing Tool (AFL) at this time is very important. Especially when landing in bad weather and at night. This landing aid is very important and very necessary for a pilot to help land the plane. In addition, flight schools, especially Poltekbang Surabaya, must understand and know what the functions and uses of these landing aids are. Starting from components to maintenance. In addition, in small airports there are still very few landing aids, perhaps due to the cost or operation, therefore this tool is designed to assist cadets in introducing what AFL equipment is like and hopefully this tool can be useful for airports that do not yet have one. AFL.